Ancient Wardrobe Studies: The Wardrobe of Kroniaina from Tebtynis (AD 54) - Dross-Krüpe, Kerstin; Wagner, Yvonne (Archaeological Textiles Review, 2013)
Documentary sources like papyri provide information about all kinds of ancient social and economic processes, especially in the Roman world. They are a valuable and unique source on the basis of which not only aspects of legal history but also of social and economic history can be investigated. In this study the province of Egypt with its abundance of papyrological evidence is used as a case study to gain insight into the relevance of textiles in ancient marriage arrangements. Apart from jewelry and household items, textiles were the most important items of a woman’s dowry and therefore often mentioned in detail in the contracts concluded between husband and wife. They are our only textual evidence of documentary nature showing textiles actually worn by women in everyday-life. Being a highly interesting type of sources in itself, the marriage and dowry contracts preserved will be used to shed light on the value, kind, number and colour of women’s textiles in imperial Egypt. After a general introduction into the source material, we will demonstrate the potential insights dowry contracts can provide with regard to tracking everyday female clothing in Roman Imperial Egypt.